New Discourses developing around the management of intangible assets in companies: the evolution of commercial and corporate brands in Spain - Soloaga,Paloma Diaz (2017)
This paper gives an up-to-date analysis of trends in managing intangible assets reflecting the various agents comprising the communication system in Spain. To this end, qualitative techniques were applied (Delphi questionnaires and in-depths interviews) on the understanding that the best way to find out the underlying reasons for a change and its subsequent consequences is to examine quality over quantity. Experts and academics, professionals in brand communication, advertisers and media managers replied to questions on the current method of managing a company's intangible assets and thus define the discourse issued from corporations and commercial brands to their stakeholders. Analysis of the results will enable us to confirm that we are certainly looking at a new communication scenario, if not a change in paradigm.